2003
DOI: 10.1260/030952403773617481
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Speed Wind Turbines with Doubly-Fed Induction Generators Part IV: Uninterrupted Operation Features at Grid Faults with Converter Control Coordination

Abstract: A model of variable-speed wind turbines equipped with doubly-fed induction generators (DFIG) and controlled by partial-load frequency converters described in [1,2] is applied in power stability investigations. A technical feature of uninterrupted operation at grid disturbances of large wind farms with such variable-speed wind turbines is suggested and discussed. This technical feature is based on fast re-start of the rotor converter, which blocks at grid faults. The main reactive power control is organised by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 9 publications
0
39
0
1
Order By: Relevance
“…According to (13) and (14), the bode plot of the closed loop torque transfer function is derived as shown in Fig. 6.…”
Section: Fig 5 Control Scheme Of Eesgmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (13) and (14), the bode plot of the closed loop torque transfer function is derived as shown in Fig. 6.…”
Section: Fig 5 Control Scheme Of Eesgmentioning
confidence: 99%
“…In [12], the rotation speed feedback algorithm is introduced to reduce the speed variation of the generator. Akhmatov [13] indicated that the pitch control method was not suitable to prevent mechanical resonance because its bandwidth was much lower, and the effective method was to utilize the electromagnetic torque. Hua Geng [14] compared the mechanical damping performances of three power control strategies for the PMSG.…”
Section: Introductionmentioning
confidence: 99%
“…[11] shows that absence or insufficient tuning of this PI controller may lead to self-excitation of the drive train system and to a risk of grid power tripping as protection against vibrations in the mechanical construction. The pitch control system is not able to damp the torsion oscillations, because of several delay mechanisms in the pitch [12]. The pitch control damps the slow frequency variations in the generator speed.…”
Section: B Dfig Control Under Grid Faultsmentioning
confidence: 99%
“…The pitch control system is not able to damp the torsional oscillations, because of several delay mechanisms in the pitch [12]. The pitch control damps the slow frequency variations in the generator speed, while the damping controller is able to damp the fast oscillations in the generator speed.…”
Section: Dfig Control Under Grid Faultsmentioning
confidence: 99%